DEVELOPMENT OF ECO-FRIENDLY LUBRICATING GREASE FROM PALM KERNEL OIL WITH POLYPROPYLENE ADDITIVE: A SUSTAINABLE APPROACH - Ugochukwu Chukwuemerie Wisdom; Ibe Raymond Obinna; Nnadikwe Johnson; Iheme Chigozie (SEAN Institute, 2025)
This study explores the development of eco-friendly lubricating grease from palm kernel oil with polypropylene additive, adopting a sustainable approach. The research focuses on formulating high-performance greases suitable for industrial and automotive applications. Through experimental synthesis and testing, including worked penetration, dropping point, and water washout resistance, the study evaluates the grease's properties. Results show that the formulated grease with polymer additive exhibits improved thermal stability (dropping point of 187°C) and suitable consistency (worked penetration of 250), meeting NLGI Grade 2 and 3 standards (Table 4.3). The grease also demonstrates excellent water resistance and anti-wear characteristics. This research contributes to sustainable lubrication science, offering a viable alternative to conventional greases and supporting environmentally friendly practices in various industries..